Deposition-precipitation versus anionic-exchange Au/Al2O3 catalysts: a comparative investigation towards the selective reduction of NOx - Nguyen, D. L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Catalysis Communications, 2012)
Catalytic properties of supported gold catalysts on gamma-Al2O3 prepared by a conventional deposition-precipitation method were compared with those obtained by anionic-exchange for the reduction of NOx by hydrocarbon under lean conditions that simulate Diesel engine exhaust gas. Interestingly, a catalytic activity enhancement is observed after thermal ageing under reactive conditions at 500 degrees C on anionic-exchanged samples which make them suitable for practical developments. On the other hand, the reverse trend is observed on the solids prepared by deposition-precipitation which deactivate at low temperature. Such changes in catalytic properties have been tentatively explained on the basis of textural and structural modifications taking place during thermal ageing under wet atmosphere. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Anionic-exchange; Au catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Promising stability of gold-based catalysts prepared by direct anionic exchange for DeNO (x) applications in lean burn conditions - Nguyen, D. -L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Topics in Catalysis, 2013)
Supported gold catalysts on gamma-Al2O3 have been investigated in the catalytic reduction of NO (x) in simulated Diesel exhaust gas conditions. Different parameters have been examined essentially the mode of gold incorporation via classical deposition-precipitation and anionic exchange methods and the nature of the pre-activation thermal treatment. The resistance to thermal ageing under reactive conditions at 500 A degrees C was found completely different with a significant rate enhancement on anionic-exchange samples. Further comparisons also show that the nature of the pre-activation thermal treatment influences the extent of surface reconstructions during thermal ageing with a detrimental effect of reductive pre-treatment on the catalytic performances.
Keywords: Anionic-exchange; Au/Al2O3 catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR